Different Rating of Global Rheumatoid Arthritis Disease Activity in Rheumatoid Arthritis Patients With Multiple Morbidities. Issue 4 (29th March 2017) - Radner, Helga; Yoshida, Kazuki; Tedeschi, Sara; Studenic, Paul; Frits, Michelle; Iannaccone, Christine; Shadick, Nancy A.; Weinblatt, Michael; Aletaha, Daniel; Smolen, Josef S.; Solomon, Daniel H.
Abstract : Objective: To quantify differences and determine the factors contributing to the difference in patient global assessment of rheumatoid arthritis (RA) disease activity (PtGA) between RA patients with multiple morbidities (RA‐MM) and those with RA only. Methods: We compared the PtGA between RA‐MM patients and those with RA only, followed up in a longitudinal cohort (n = 1, 040). In analyses performed on RA‐MM patients (n = 575) and those with RA only (matched for swollen joint count, tender joint count, evaluator global assessment, and disease duration), the mean difference in PtGA (ΔPtGA) between the 2 groups was assessed. The contribution of patient characteristics to the explained variation of ΔPtGA in the matched cohort was calculated as semipartial R 2 and summarized as the percentage of the total R 2 in linear regression models. Results: RA‐MM patients reported higher (or worse) PtGA, with an increased PtGA associated with more morbidities ( P for linear trend < 0.01); this relationship remained significant after adjustment for disease activity, age, and disease duration. After matching 294 RA‐MM patients to those with RA only, the pairwise comparison of mean PtGA (on a scale of 0–100 mm) was significantly higher (worse) for RA‐MM patients (mean ± SD 30.5 ± 24.3) versus those with RA only (25.6 ± 22.9) (mean ΔPtGA 4.9 ± 26.7; P < 0.01 by paired t ‐test). Variables uniquely contributing to ΔPtGA were fatigue (18%), pain (17%), and modified Health Assessment Questionnaire scores (9%). Conclusion: In RA patients with multiple morbidities, the perception of RA disease activity as measured by the PtGA might be impacted by the burden of multiple diseases in one individual. RA‐MM patients have higher (worse) levels of PtGA scores compared to patients with RA only. The difference in PtGA is mainly explained by differences in fatigue and pain.